The effect of host society culture on migrant wage discrimination: Approaching the Roestigraben - Pierre Kohler (Graduate Institute of International and Development Studies, 2012)
This paper investigates whether host society culture affects migrant wage discrimination, i.e. whether migrant wage discrimination is more intense in host societies where culture is more inward-looking. The motivation for this investigation in the Swiss context stems from two stylized facts showing that (i) political preferences on issues related to migration, asylum and naturalization of foreigners are markedly more conservative in the German region and (ii) that average wage differences between migrants and natives are larger in the German region. Building on this, the paper begins with a comparison of returns to factors (for eight migrant groups compared to natives) using a human capital model of wage determination. It then performs an Oaxaca decomposition of wage differentials in order to compare its unexplained component across groups and regions. The last step consists in implementing a regression discontinuity design approach to establish whether host society culture is one of the determinants explaining differences in migrant wage discrimination across the language border. Results show returns to factors of wage-earning migrants are lower in the German region for a preponderant majority of migrant groups. The analysis of wage differentials and the associated unexplained parts also support the hypothesis that wage discrimination is more pronounced in this region of the Swiss labor market. Finally, results of the regression discontinuity design approach confirm that host society culture is one of the determinants of wage discrimination endured by migrants.
Keywords: F22; J15; J31; J60; J68; J71; Z10; Z13; 330; immigration; migration; labour market; culture; political preferences; wage discrimination; Switzerland; Einwanderung; Lohndifferenzierung; Migranten; Gesellschaftliches Bewusstsein; Politische Kultur; Schweiz